Surgical management of non-obstetric vulvar hematoma in a pediatric patient: A Case Report - Singh, Karnel; Maritha, Indah Dina (Jurnal Ilmiah Kesehatan Sandi Husada, 2025)
Introduction: Vulvar hematoma is an uncommon condition in pediatric patients, often caused by blunt trauma to the perineum. Its management differs from that in adults due to the anatomical and physiological characteristics of children. Proper diagnosis and treatment are essential to prevent complications such as necrosis, infection, or recurrent bleeding. Methods: An 11-year-old girl presented with pain and swelling in the genital region following a fall in a sitting position with a mobile phone underneath her. Physical examination revealed a right-sided vulvar hematoma measuring 7×7×5 cm. Due to the progressive enlargement and pain, surgical evacuation was performed under anesthesia, followed by drainage and wound suturing with vicryl 2.0 thread. Postoperative management included pediatric co-treatment, analgesics, and antibiotics. Results: The patient showed significant improvement within three days post-surgery, with reduction in swelling and pain. The drain was removed on the second postoperative day, and wound healing progressed well without complications. The case emphasizes the importance of prompt intervention to prevent pressure necrosis and infection, especially in large hematomas or those with progressive symptoms. Conclusion: Non-obstetric vulvar hematoma, although rare in children, requires prompt evaluation and management. Surgical evacuation is recommended for large or progressively enlarging hematomas to prevent necrosis and other complications. Appropriate surgical technique, postoperative care, and interprofessional collaboration ensure optimal patient outcomes